Analysis of Factors Affecting the Bed Occupancy Rate (BOR) in Inpatient Services at Dr. J. H. Awaloei Tateli Hospital - Ade Pratiwi Tubagus; Dwi Widya Pujiastuti; Gustian Rante Tiballa; James Klemens Phieter Phie (Journal Research of Social Science, Economics, and Management, 2026)
Inpatient services are an important component in the operational performance of hospitals that reflect the efficiency of bed utilization. Bed Occupancy Rate (BOR) as the main indicator does not stand alone, but is influenced by other indicators such as Turn Over Interval (TOI), Average Length of Stay (AVLOS), Bed Turn Over (BTO), and the number of hospitalized patients (MRS). This study aims to analyze the factors that affect BOR in inpatient services at dr. J. H. Awaloei Tateli Hospital. The study used an analytical quantitative design with a cross-sectional approach using secondary data for the period March 2025–February 2026 with 84 units of inpatient analysis units per month. The analysis was conducted univariately, bivariately using the Spearman test, and multivariate using multiple linear regression. The results showed that the average BOR was 57.16%, TOI was 3.2 days, AVLOS was 3.28 days, MRS was 240 patients, and BTO was 7.85 times. Bivariate analysis showed that TOI (r=-0.881; p<0.001), BTO (r=0.705; p<0.001), and MRS (r=0.779; p<0.001) were significantly related to BOR, while AVLOS was insignificant (p=0.375). Multivariate analysis showed that TOI (B=-6.485; p<0.001), AVLOS (B=5.353; p=0.005), MRS (B=0.194; p<0.001), and BTO (B=-8.064; p<0.001) had a significant effect on BOR simultaneously with an R² value of 0.784. BOR is significantly influenced by TOI, AVLOS, MRS, and BTO, with TOI being the most consistent factor influencing BOR.